การปรับปรุงพันธุ์ลูกผสมข้ามชนิดของทานตะวันโดยใช้ลักษณะเกสรเพศผู้เป็นหมัน - เหนือสุข ชนม์นิภา; เตชะศีลพิทักษ์ ธัญญะ; สุขประเสริฐ พัฒนา; จันจุฬา ณัฐพงค์; บาลลา นุชรัฐ (Thai Journal of Science and Technology, 2018)
Abstract Interspecific hybrid sunflowers were produced using male sterile plants of 2 species; Helianthus annuus featuring short stems, bright colored flowers and 1-2 flowers per plant, and Helianthus debilis featuring spindly stems and many flowers per plant. The experiment to develop an interspecific hybrid sunflower with male sterile pollen was conducted from January, 2017 to April, 2018 at the field laboratory of the Department of Horticulture, Kasetsart University, Bangkok. H. annuus ‘A-line’ and ‘B-line’ were used to maintain male sterility and were cross pollinated with H. debilis. Male sterility was found in 72.5 percent of the interspecific hybrid sunflowers produced. The interspecific plants stem height averaged 102.07 centimeters, with 17 flowers per plant with flowers size and disk flowers size of 9.89 and 2.62 centimeters respectively. Interspecific hybrid sunflowers can be used as bedding plants and in ornamental sunflower breeding. Keywords: bedding plant; cross-pollination; interspecific hybrid